ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TAX COMPLIANCE TERHADAP PENYAMPAIAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI - Mela cyntia Sani; Khuznatul Zulfa Wafirotin; Ika Farida Ulfa (ISOQUANT : Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
Individual Taxpayers (WPOP) experience problems every year due to difficulties in filling out SPT. The Directorate General of Taxes issued a new policy in providing easy Notification Services (SPT) using online systems namely e-Filling and e-SPT. The policy taken by the government turned out that there were still many obstacles faced by the KPP Pratama Ponorogo Tax Office regarding ponorogo's lack of understanding related to filling out SPT manually or online using e-SPT and e-Felling. So that this certainly can make taxpayers object to the submission of Annual Tax Returns, especially in terms of calculating the tax payable which must be calculated on its own. Data collection is done by using primary data in the form of questionnaires. The samples processed in this study were 100 respondents who were distributed to individual taxpayers registered at KPP Pratama Ponorogo. Data analysis method uses validity test and reliability test, hypothesis testing using multiple linear regression analysis. The results of this study indicate that the awareness of taxpayers, taxpayer intentions, taxpayer attitudes, subjective norms, behavioral control and ease of tax return filling process affect Tax Compliance (tax compliance) submission of Annual Tax Returns. This is because taxpayers know, understand and implement taxation provisions correctly and voluntarily so as to increase taxpayer compliance in fulfilling their obligations and are willing to report taxes with their own awareness.